DIGITAL IMAGE COMPRESSION APPROACHES: A CASE STUDY - Firas S. Abdulameer (European Journal of Research Development and Sustainability, 2023)
Digital images require a vast number of bits to represent them, and their canonical representation typically contains a substantial degree of redundancy. By taking advantage of these redundancies, image compression algorithms lower the number of bits necessary to represent an image. In order to overcome this redundancy, this paper discusses several image compression approaches and their advantages